1996
DOI: 10.1103/physrevb.54.14807
|View full text |Cite
|
Sign up to set email alerts
|

Phonon contributions to photohole linewidths observed for surface states on copper

Abstract: We have observed the linear temperature dependence of the linewidth of surface states on Cu. These data allow the determination of a temperature coefficient for the phonon-hole coupling, which enters the linewidth as ⌫ϭ2bk B T. For the s,p-like ͑Shockley͒ state at ⌫ on Cu͑111͒, we find bϭ0.137Ϯ0.015, in perfect agreement with earlier data of McDougall, Balasubramian, and Jensen ͓Phys. Rev. B 51, 13 891 ͑1995͔͒. The d-like ͑Tamm͒ state at M on Cu͑111͒ is characterized by a different bϭ0.085Ϯ0.015, which, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 29 publications
7
43
0
Order By: Relevance
“…This deficiency of PES is well known; it could be attributed to broadening by scattering at substrate imperfections. 20,30,34 In agreement with this interpretation, Li et al in a recent STS study on Ag͑111͒ reported an unprecedented small ⌫ value from local measurements on surface areas that were bare of defects. 31 In Fig.…”
Section: Spatial Damping On Cu"111…supporting
confidence: 55%
See 2 more Smart Citations
“…This deficiency of PES is well known; it could be attributed to broadening by scattering at substrate imperfections. 20,30,34 In agreement with this interpretation, Li et al in a recent STS study on Ag͑111͒ reported an unprecedented small ⌫ value from local measurements on surface areas that were bare of defects. 31 In Fig.…”
Section: Spatial Damping On Cu"111…supporting
confidence: 55%
“…This assignment is supported by differences of up to 10 meV in the linewidth ''offset'' between different research groups, whereas there is good agreement on d⌫/dT. 10,20 The influence of sputter defects on the linewidth ⌫ was employed to extrapolate to ''intrinsic'' linewidths expected from PES of perfectly ordered surfaces. 30 The resulting ''intrinsic''…”
Section: Spatial Damping On Cu"111…mentioning
confidence: 89%
See 1 more Smart Citation
“…The temperature dependence of the linewidth for photoemission from d-like surface states has also been studied by Matzdorf et al [129]. Observed mass enhancement factors are l ¼ 0:09 AE 0:02 at M on Cu(1 0 0) and l ¼ 0:085 AE 0:015 at M on Cu (1 1 1).…”
Section: Tamm States On Noble-metal Surfacesmentioning
confidence: 91%
“…Observed mass enhancement factors are l ¼ 0:09 AE 0:02 at M on Cu(1 0 0) and l ¼ 0:085 AE 0:015 at M on Cu (1 1 1). The latter value may be compared with l ¼ 0:14 AE 0:02 [99] and l ¼ 0:137 AE 0:015 [129], respectively, measured for the Shockley state at G on Cu (1 1 1). All values are of comparable magnitude and indicate that the surface states at G and M, despite their different orbital character and the corresponding different localization, respond similarly in their electron-phonon interaction.…”
Section: Tamm States On Noble-metal Surfacesmentioning
confidence: 99%